Assessing the Diversity and Distribution Pattern of the Speciose Genus Lycocerus (Coleoptera: Cantharidae) by the Global-Scale Data - Liu, Tong; Liu, Haoyu; Wang, Younan; Xi, Huacong; Yang, Yuxia (Frontiers in Ecology and Evolution, 2022)
Species richness patterns and endemism on the large-scale play a significant role in biogeography and biodiversity conservation. This study aimed to explore the diversity centers and endemic areas of a large cantharid genus Lycocerus, so as to test whether the hypothesis of montane and island systems biodiversity in previous studies was supported. Here, a comprehensive species’ geographical database on the global scale consisting of 4234 records for 324 Lycocerus species was compiled and analyzed in this study. Species richness pattern was mapped into a grid-based map with a spatial resolution of 1° × 1° fishnet. An unbalanced pattern was identified, and it showed that the centers of species richness of Lycocerus were situated in Eastern Himalayas, Hengduan Mountains, Eastern Sichuan Mountains, Taiwan and Japan. Further analyses based on two approaches, including parsimony analysis of endemicity (PAE) and endemicity analysis (EA), were applied to detect areas of endemism (AOEs) at three different grid sizes (1°, 1.5°, 2°). Finally, a total of nine AOEs were detected, including five montane areas (Himalayan areas, Hengduan Mountains, South edge of China, Eastern China Mountains, Eastern Sichuan Mountains), three islands (Taiwan Island, Japan, Korean Peninsula) and one plateau (Shan Plateau), which were generally consistent with the species richness pattern. The results verify that montane and island systems have an essential role in promoting the formation of diversity centers and AOEs because of their complex topography, varied habitat and geological events.